Harry A. Bullis and the private organization of liberal internationalism, 1932-1962 - Kestner, John (My University, 1990)
Contents include: the corporation and the individual; a fortress in a collapsing world; building the base; Korea, crisis, and the private selling of NSC-68; the ties that blind; and conclusions, the limits or organization.
[ii], 139 leaves ; 29 cm.